The production, purification and characterization of endo-1,4-ß-mannanase from newly isolated strains from Scopulariopsis candida - Mudau, Maria Mabyalwa (University of the Free State, 2006)
Mannan polysaccharides occur in hemicellulose fraction of the plant cell walls. The hydrolysis of these polymers involves the action of enzymes such as β-mannanase, β-mannosidase and α- galactosidase which are produced by both fungi and bacteria. The current study reports on the production of β-mannanase, β-mannosidase and α-galactosidase by newly isolated Scopulariopsis candida strains LMK004 and LMK008. The effect of medium composition and carbon source on growth and enzyme production was evaluated in a liquid culture. A combination of Vogel’s medium and locust bean gum was found to stimulate growth and increase β-mannanase production. Optimal β-mannanase production of 7800 nkat/g biomass for LMK004 and 13300 nkat/g biomass for LMK008 was achieved in media containing 10% NaCl, 1X Vogel’s medium, 1% yeast extract and 1% locust bean gum. Both strains secreted trace amounts (less than 1 nkat/ml) of β-mannosidase and α-galactosidase indicating that these enzymes may be retained intracellularly. Native-PAGE and SDS-PAGE were used together with the zymogram to assess purity and to estimate the molecular weight of the proteins. The molecular weight of LMK004 β-mannanase was estimated to be ≈41 kDa whereas that of LMK008 β-mannanase could not be determined due to excessive loss of protein material during dialysis. The β-mannanase from LMK004 was most active at pH 5 and 50 °C, and retained ≥ 80% of its activity at pH 5 – 6.5 after 24 hrs of incubation at 4 °C. In contrast, the LMK008 β- mannanase retained ≥ 60% activity between pH 6 – 7. Both enzymes remained stable for 3 hrs at temperature between 30 °C and 40 °C, and showed loss of activity at higher temperatures. The two enzymes displayed different degrees of halotolerance. The LMK008 β-mannanase tolerated high NaCl concentrations with 60% activity remaining after incubation for 2 hrs at 20% NaCl, whereas the LMK004 β-mannanase was only active between 0% - 10% NaCl. It is clear from the current study that the two strains of S. candida produce distinct β-mannanases which may be useful candidates in low water activity reactions.

Mannaanpolisakkariede kom voor in die hemisellulose fraksie van plantselwande. Ensieme soos β-mannanase, β-mannosidase en α-galaktosidase, geproduseer deur beide fungi en bakterië, is betrokke by die hidrolise van hierdie polimere. Hierdie studie handel oor die produksie van β- mannanase, β-mannosidase en α-galaktosidase deur nuwe isolate van Scopulariopsis candida, stamme LMK004 en LMK008. Die invloed van mediumsamestelling en koolstofbron op groei en ensiemproduksie is geëvalueer in n vloeibare kultuur. Daar is gevind dat ‘n kombinasie van Vogel se medium en locust bean gum groei stimuleer en produksie van β-mannanase verhoog. Optimale b-mannanase produksie van 7800 nkat/g biomassa vir LMK004 en 13300 nkat/g biomassa vir LMK008 is verkry in media bestaande uit 10% NaCl, 1X Vogel se medium, 1% gisekstrak en 1% locust bean gum. Beide stamme het spoorhoeveelhede (minder as 1 nkat/ml) β- mannosidase en α-galaktosidase uitgeskei, wat daarop mag dui dat hierdie ensieme intrasellulêr behou word. “Native”-PAGE en SDS-PAGE is saam met zymogram gebruik om die suiwerheid en molekulêre massas van die proteïene te bepaal. Die molekulêre massa van die LMK004 β- mannanase is ≈41 kDa terwyl dié van die LMK008 β-mannanase nie bepaal kon word nie van weë n uitermatige verlies van proteïen gedurende dialise. Die LMK004 β-mannanase was mees aktief by pH 5 en 50 oC en het ≥ 80% aktiwiteit behou by pH 5 – 6.5 na 24 uur inkubasie by 4 oC. Inteenstelling daarmee, het die LMK008 β-mannanase ≥ 60% aktiwiteit behou by pH 6 - 7. Beide ensieme was stabiel vir 3 ure by temperature tussen 30 oC en 40 oC en het n verlies aan aktiwiteit getoon by hoer temperature. Die twee ensieme het verskilende grade van halotoleransie getoon. Die LMK008 β-mannanase kon hoer NaCl konsentrasies verduur met 60% aktiwiteit na inkubasie vir 2 ure by 20% NaCl, waa die LMK004 β-mannanase slegs aktief was tussen 0% - 10% NaCl. Uit hierdie studie blyk dit duidelik dat die twee stamme van S. candida erskillende β-mannanases produseer wat nuttig mag wees in reaksies by lae wateraktiwiteite.
Dissertation (M.Sc. (Microbial, Biochemical and Food Biotechnology))--University of the Free State, 2006
Keywords: Fungi -- Identification; Plectomycetes; Polysaccharides -- Biodegradation; Enzymes; Salt pan; Production; Purification; ß-mannanase; Characterization; Scopulariopsis candida